2019
DOI: 10.1159/000501016
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Integrase Resistance among Highly Antiretroviral Experienced Patients from Morocco

Abstract: <b><i>Background:</i></b> We aimed to analyze for the first time in Morocco the integrase (IN) sequence variability among highly experienced HIV-1-infected patients with no prior IN strand transfer inhibitor (INSTI) exposure who failed on reverse transcriptase inhibitors and protease inhibitors. <b><i>Methods:</i></b> The HIV-1 IN region was sequenced from plasma samples of all 78 recruited patients. The amino acid IN sequences were HIV-1 subtyped and screened fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…In this study, many amino acid polymorphisms that are different from the standard B subtype strains were detected in both the CRF01_AE and CRF07_BC strains, which have also been reported in untreated persons who are infected with other genotype strains in other countries ( Brado et al, 2018 ; Alaoui et al, 2019 ; Huang et al, 2019 ; Lai et al, 2021 ). Although these polymorphic variants were encountered in more than half of the studied participants, other polymorphic mutations that probably have no effect on INSTIs susceptibility were reported in previous in vitro studies, and clinical trials showed different frequencies ( Kobayashi et al, 2011 ; Casadellà et al, 2015 ).…”
Section: Discussionsupporting
confidence: 67%
“…In this study, many amino acid polymorphisms that are different from the standard B subtype strains were detected in both the CRF01_AE and CRF07_BC strains, which have also been reported in untreated persons who are infected with other genotype strains in other countries ( Brado et al, 2018 ; Alaoui et al, 2019 ; Huang et al, 2019 ; Lai et al, 2021 ). Although these polymorphic variants were encountered in more than half of the studied participants, other polymorphic mutations that probably have no effect on INSTIs susceptibility were reported in previous in vitro studies, and clinical trials showed different frequencies ( Kobayashi et al, 2011 ; Casadellà et al, 2015 ).…”
Section: Discussionsupporting
confidence: 67%
“…In this study, many amino acid polymorphisms that are different from the standard B subtype strains were detected in both the CRF01_AE and CRF07_BC strains, which have also been reported in untreated persons who are infected with other genotype strains in other countries (Brado et al, 2018;Alaoui et al, 2019;Lai et al, 2021). Although these polymorphic variants were encountered in more than half of the studied participants, other polymorphic mutations that probably have no effect on INSTIs susceptibility were reported in previous in vitro studies, and clinical trials showed different frequencies (Kobayashi et al, 2011;Casadellà et al, 2015).…”
Section: Patients Codeidsupporting
confidence: 65%
“…A month later, the viral load was undetectable, and after about 8 months, a pair of novel mutations T97A and S147G in IN were detected (Wainberg and Han 2015b , a ). These outcomes propose that DTG should be used with caution in INSTI salvage therapy for RAL failures or in patients with multiple RAMs (Alaoui et al 2019 ).…”
Section: Computational Studiesmentioning
confidence: 99%